Gender Violence, Gender Justice and Gender-Based Laws: An Analysis of Pattern and Policies in India and Indonesia - Tyagi, Neelam (Brawijaya Law Journal, 2020)
If we look at the status of women in a particular society, we can get a fair idea about its social organization and its standard. Violence against women is a challenge against the right to equality and an extreme form of violation of human rights. From ancient times to the modern era, women face discrimination, exploitation, and violence in every walk of their life, and this phenomenon is prevalent across all borders. Every civilized society tries to protect its members both in public and private spaces with the help of a set of laws and rights. Hosts of laws and beneficial legislation enacted to ameliorate womenâ€™s condition have failed to achieve the desired purpose due to the presence of several factors. Thus mere enactment of laws will not serve the desired purpose until they are effectively implemented and assertively claimed by women. This paper presents an analysis of the various forms of violence that women face throughout their life and lacunas in the laws made for dealing with them. It analyses the extent to which the women favoring laws in India and Indonesia prevents the frequency of their occurrence along with some recommendations for bringing about changes on this situation.Â